Application of Google Classroom with Flipped Classroom Learning Model on Student Learning Outcomes at SMK Unitomo Surabaya - Happy Indra Chusnuraafi; Ekohariadi Ekohariadi; Joko Joko; Marniati Marniati (EduLine: Journal of Education and Learning Innovation, 2022)
Research that uses the Flipped Classroom model is an implementation of Blended Learning. This study aims to find out how to apply Google Classroom with the Flipped Classroom learning model in schools on student motivation, student activities, and student learning styles. This study started from distributing questionnaires, collecting data, analyzing data and drawing conclusions. This study used a quantitative approach with an experimental research model with a student population at SMK UNITOMO Surabaya. Data analysis using multiple linear regression using SPSS. Based on the test results, the data shows the F value of 3.164 which is greater than the F table with a significant value of 0.039. So, it can be concluded that from student motivation, student activities, and student learning styles have a significant impact on student learning outcomes using the Flipped Classroom learning model using the Google Classroom application at SMK UNITOMO Surabaya.